Toxicity Removal of Pharmaceuticals Mixtures through Electron Beam Irradiation - NAthalia Fonseca Boiani; Flávio Kiyoshi Tominaga; Sueli Ivone Borrely (Brazilian Journal of Radiation Sciences)
Contamination of the aquatic environment by pharmaceuticals is becoming a global phenomenon of growing concern. Pharmaceuticals can be only partially metabolized during therapeutic use, resulting in the excretion and release of residual fractions into sewage, unaltered or in the form of metabolites they may remain active in sewage treatment facilities for a long time. Many studies have shown that wastewater treatment plants are not designed to eliminate these compounds, as such the main source of drug residues in the aquatic environment. Due to their frequency and detection in the environment, persistence and toxicity, the most studied pharmaceutical groups are antibiotics, psychiatric drugs, hormones, analgesics and anti-inflammatory, β-blockers, and antidiabetic drugs. Advanced Oxidative Processes (AOPs) have been applied as an alternative or complement to conventional sewage treatment processes, aiming the degradation and removal of toxic pollutants. Electron beam irradiation (EBI) is considered a clean process that offers an environmentally friendly alternative to degrade pollutants in the aquatic environment. This technology has been demonstrated effective for removal of multiclass pharmaceutical residues present in wastewater by using low doses (2.5-5.0 kGy). In this present study, we focused on toxicity removal of three different tertiary mixtures of pharmaceuticals, which showed toxicity removal efficiency around 80% for the mixture of Propranolol, Fluoxetine and Diclofenac; 75% for the mixture of  Propranolol, Fluoxetine and Sulfadiazine; and 30% for the mixture of Acetylsalicylic acid, Fluoxetine and Metformin.